The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1159/000301658
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Changes in the Reproductive Tissues of Ewes during Pregnancy

Abstract: The blood flows to reproductive organs were measured by means of radionuclide-labeled microspheres in 24 pregnant ewes with gestational ages ranging from 38 to 141 days. The microspheres were injected in the left ventricle of the non-anesthetized animal 4–7 days after surgery and while uterine blood flow was recorded continously by means of electromagnetic probes on both uterine arteries. The blood flow to ovaries with corpus luteum was maximum in early pregnancy and greater than in ovaries without corpus lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
110
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(115 citation statements)
references
References 11 publications
4
110
0
1
Order By: Relevance
“…Furthermore, both sets of data are similar to the observations of Stegeman (1974) both in pattern and magnitude of the increase in placental vascularization that she determined using a microscopic point counting method. Moreover, the increases in placentome capillary area density and in cotyledonary capillary number and surface density from early to late gestation are in broad agreement with previously documented cross-sectional measurements of changes in uterine (maternal) and umbilical (fetal) blood flows in vivo, measured at mid and late gestation (Rosenfeld et al 1974, Molina et al 1990.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, both sets of data are similar to the observations of Stegeman (1974) both in pattern and magnitude of the increase in placental vascularization that she determined using a microscopic point counting method. Moreover, the increases in placentome capillary area density and in cotyledonary capillary number and surface density from early to late gestation are in broad agreement with previously documented cross-sectional measurements of changes in uterine (maternal) and umbilical (fetal) blood flows in vivo, measured at mid and late gestation (Rosenfeld et al 1974, Molina et al 1990.…”
Section: Discussionsupporting
confidence: 89%
“…Since placental estrogen synthesis is substantial throughout pregnancy, local tissue concentrations probably exceed plasma levels. Exogenous estrogen increases uteroplacental blood flow 40-50% in a pattern similar to that seen in nonpregnant animals (4,9).This also occurs after substrate-induced increases in endogenous placental estrogen production (4,(55)(56)(57). Although we have confirmed that E 2 ␤ increases UBF in pregnant ewes and have now demonstrated that, as in nonpregnant animals, this is associated with a rise in uterine venous cGMP, these data do not provide conclusive evidence that local estrogens are necessary for maintaining blood flow.…”
Section: Discussionmentioning
confidence: 66%
“…However, it was not until the studies of Killam et al (5), using chronically instrumented nonpregnant ewes studied remote from surgery and anesthesia, that the magnitude of these effects on the uterine vascular bed were clearly demonstrated, uterine blood flow (UBF) 1 increasing Ͼ 10-fold after 1 g/kg of intravenous (iv) estradiol-17 ␤ (E 2 ␤ ) rather than the 50-100% previously reported (4, 6, 7). Rosenfeld et al (4,8,9), using the microsphere technique for measuring regional blood flows, not only confirmed these observations, but also demonstrated that E 2 ␤ had significant vasodilatory effects on several nonreproductive as well as reproductive tissues in nonpregnant, pregnant, and postpartum sheep and increased cardiac output 15-20%, thereby demonstrating substantial systemic responses. Importantly, the uterine responses to E 2 ␤ are locally mediated and independent of its effects on systemic vascular resistance (5,10,11).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…4.3 days of gestation (term -145 days), respectively. The surgical procedure for the preparation of the chronically instrumented sheep model has been previously described in detail (18,19). In brief, after sedation with intravenous ketamine hydrochloride (2 mg/kg), spinal anesthesia was induced with hyperbaric pontocaine hydrochloride (12 mg) and supplemented with intravenous sodium pentobarbital as needed (1 5 mg/kg).…”
mentioning
confidence: 99%